Os fatores sociodemográficos e o desempenho escolar: uma análise a partir do processo de expansão do Instituto Federal do Espírito Santo - Ramos, Anderson Chagas (2024)
The present study analyzes the results of large-scale evaluations of federal education in Espírito Santo between 2009 and 2022. Based on indicators from the cities where the schools are located, the aim is to identify the sociodemographic factors that are most related to the average performance of students. students. Considering that federal public education has a good impact in terms of quality and is recognized inside and outside Brazil, a significant increase in students has been observed over the last 15 years due to the federal network expansion program. As a result, the increase in enrollments, through the creation of new teaching units, expanded its physical structure, providing greater access to technical education, linked to secondary education, mainly in interior locations. All this effort was aimed at expanding the right to education and better training Brazilian society in a school network recognized for its quality. From this, this research analyzed how this expansion occurred, demonstrating the criteria for establishing new units and evaluated the average performance of students in this process based on the analysis of large-scale assessments promoted by INEP through ENEM. From the results found, it was possible to identify that there are sociodemographic factors in the municipalities that are related to the average performance of students' grades through the application of statistical methods. This made it possible to develop a model that allows municipalities to be evaluated for the construction of new school units based on a performance projection based on the results of current schools. The research was limited to the state of Espírito Santo in the period from 2009 to 2022. Thus, through the information obtained, the research makes it possible to improve the processes for choosing the best locations for installing new schools.